Cabotage Act and the Challenges of Nigerian Shipping Lines in Sub-Sahara Africa - Nwekeaku, Charlie; Atteh, John (Advances in Social Sciences Research Journal, 2016)
This article is set to investigate the factors militating against the utilization of the Nigerian Cabotage Act 2003 to revamping the ailing shipping industry, which is the fulcrum of the Nigerian major oil and gas sector of the economy. Secondary data, generated through document reading, were used for the analysis. A critical study of both the Act and shipping lines revealed inherent structural defects (poor administration and technology respectively), which are dissonant with the primary aims of developing and protecting local content in shipping industry. The complexities of this resulted to foreign re-infiltration of the Nigerian shipping industry with consequent capital loss. With the existing scenario and the ultimate necessity to overhaul the industry to full benefits of Nigeria and her entire citizenry, there is need to review the Act in order to accommodate the dynamism and interdependence of the modern global market. Also, efforts should be made to create an enabling ground for Nigerians to adequately adjust and take advantage of the Act. These, unarguably, are the way forward to repositioning and guaranteeing a viable, competitive and profitable world class national shipping industry .